Photocatalytic degradation of salicylic acid on fixed TiO2 - kinetic studies - S. M. Ould-Mame; O. Zahraa; M. Bouchy (International Journal of Photoenergy)
The photocatalytic activity of TiO2 deposits (Degussa-P25 and Sachtleben-Hombikat) has been studied using salicylic acid as a model water pollutant and an UV-fluorescent lamp as a light source. Both catalysts have shown very similar properties towards the photocatalytic degradation of salicylic acid. Special attention has been given to the effect of the light flux absorption and of the pollutant adsorption. Moderate mass-transfer limitation has been found. Specific parameters of the phenomenon have then been determined for the two catalysts and a simple general expression of the rate of photocatalytic degradation has been derived.